α-Glucosidase and α-Amylase Inhibitory Potentials of Quinoline-1,3,4-oxadiazole Conjugates Bearing 1,2,3-Triazole with Antioxidant Activity, Kinetic Studies, and Computational Validation - Nosipho Cele; Paul Awolade; Pule Seboletswe; Kolawole Olofinsan; Md. Shahidul Islam; Parvesh Singh (MDPI AG, 2022)
Diabetes mellitus (DM) is a multifaceted metabolic disorder that remains a major threat to global health security. Sadly, the clinical relevance of available drugs is burdened with an upsurge in adverse effects; hence, inhibiting the carbohydrate-hydrolyzing enzymes α-glucosidase and α-amylase while preventing oxidative stress is deemed a practicable strategy for regulating postprandial glucose levels in DM patients. We report herein the α-glucosidase and α-amylase inhibition and antioxidant profile of quinoline hybrids 4a-t and 12a-t bearing 1,3,4-oxadiazole and 1,2,3-triazole cores, respectively. Overall, compound 4i with a bromopentyl sidechain exhibited the strongest α-glucosidase inhibition (IC50 = 15.85 µM) relative to reference drug acarbose (IC50 = 17.85 µM) and the best antioxidant profile in FRAP, DPPH, and NO scavenging assays. Compounds 4a and 12g also emerged as the most potent NO scavengers (IC50 = 2.67 and 3.01 µM, respectively) compared to gallic acid (IC50 = 728.68 µM), while notable α-glucosidase inhibition was observed for p-fluorobenzyl compound 4k (IC50 = 23.69 µM) and phenyl-1,2,3-triazolyl compound 12k (IC50 = 22.47 µM). Moreover, kinetic studies established the mode of α-glucosidase inhibition as non-competitive, thus classifying the quinoline hybrids as allosteric inhibitors. Molecular docking and molecular dynamics simulations then provided insights into the protein-ligand interaction profile and the stable complexation of promising hybrids at the allosteric site of α-glucosidase. These results showcase these compounds as worthy scaffolds for developing more potent α-glucosidase inhibitors with antioxidant activity for effective DM management.